Molecular Recognition‐Mediated Transformation of Single‐Chain Polymer Nanoparticles into Crosslinked Polymer Films. Issue 42 (8th September 2017) - Mahon, Clare S.; McGurk, Christopher J.; Watson, Scott M. D.; Fascione, Martin A.; Sakonsinsiri, Chadamas; Turnbull, W. Bruce; Fulton, David A.
Abstract: We describe single‐chain polymer nanoparticles (SCNPs) possessing intramolecular dynamic covalent crosslinks that can transform into polymer films through a molecular recognition‐mediated crosslinking process. The SCNPs utilise molecular recognition with surface‐immobilised proteins to concentrate upon a substrate, bringing the SCNPs into close spatial proximity with one another and allowing their dynamic covalent crosslinkers to undergo intra‐ to interpolymer chain crosslinking leading to the formation of polymeric film. SCNPs must possess both the capacity for specific molecular recognition and a dynamic nature to their intramolecular crosslinkers to form polymer films, and an investigation of the initial phase of film formation indicates it proceeds from features which form upon the surface then grow predominantly in the xy directions. This approach to polymer film formation presents a potential method to "wrap" surfaces displaying molecular recognition motifs—which could potentially include viral, cellular and bacterial surfaces or artificial surfaces displaying multivalent recognition motifs—within a layer of polymer film. Abstract : Adaptive materials : Single‐chain polymer nanoparticles possessing intramolecular dynamic covalent crosslinks can transform into polymer films through a molecular‐recognition‐mediated crosslinking process. This approach presents a potential method to "wrap" viral, cellular and bacterial surfaces within a layer of polymer film.